2019
DOI: 10.3390/ijms20246129
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reaction Mechanism of NO–CO on the ZrO2 (110) and (111) Surfaces

Abstract: Due to the large population of vehicles, significant amounts of carbon monoxide (CO), nitrogen oxides (NOx), and unburned hydrocarbons (HC) are emitted into the atmosphere, causing serious pollution to the environment. The use of catalysis prevents the exhaust from entering the atmosphere. To better understand the catalytic mechanism, it is necessary to establish a detailed chemical reaction mechanism. In this study, the adsorption behaviors of CO and NO, the reaction of NO reduction with CO on the ZrO2 (110) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This direction is represented by 39 articles [ 28 , 35 , 129 , 134 , 136 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 ]. Their distribution, according to the above types, is presented in Table 7 .…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…This direction is represented by 39 articles [ 28 , 35 , 129 , 134 , 136 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 ]. Their distribution, according to the above types, is presented in Table 7 .…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…In this research, the given reaction between cyclopentadiene and methyl acrylate was computationally investigated in the ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate, [BMIM] [PF 6 ], as a basis for the validation of the OPLS-VSIL to properly reproduce a reaction medium environment. The articles of group ( c ) include publications [ 28 , 129 , 136 , 193 , 195 , 199 , 200 , 202 , 208 , 209 , 212 , 213 , 215 , 220 ]: in most of them [ 129 , 136 , 195 , 199 , 200 , 202 , 208 , 209 , 212 , 215 ], the objects of quantum chemical calculations were the chelate and macrocyclic coordination compounds of various s -, p -, d -, and f -elements. The most significant of them seems to be publication [ 136 ], devoted to Pu(IV) and Pu(VI) complexes with tridentate (NNN)-donor-atomic ligands, in particular, di(pyridyl-2)amine, 1,3-diamino-2-azapropane, and 2,6-di(pyridyl-2) pyridine, the results of which can be very useful in the development of new extractants and organic sensors of plutonium.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the adsorption behaviors of CO on the Ce 0.875 Zr 0.125 O 2 (110) surface, we found that Zr T was the most favorable active site owing to the maximum adsorption energy. Besides, according to the adsorption energies of CO on the CeO 2 (110) surface (E ads z À0.2 eV)34,35 and ZrO 2 (110) surface (E ads z À0.6 eV),40 it also could be concluded that CO preferred to interact with Zr atoms and adsorb on the top site of Zr on Ce 1Àx Zr x O 2 (110) surfaces. However, it is noteworthy that CO adsorption on Ce 1Àx Zr x O 2 (110) surfaces were still rather weak (E ads z À0.6 eV), indicating that the feasible CO oxidation mechanism was gas-phase CO molecule directly extracting…”
mentioning
confidence: 94%